2019
DOI: 10.18410/jebmh/2019/489
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Dry Eye Among Medical Students and Its Impact on Their Mental Health: A Questionnaire Based Survey

Abstract: BACKGROUND Dry eye is a common disease affecting worldwide. Dry eye is defined as a multifactorial disease of tears and ocular surface that results in discomfort, visual disturbance and tear film instability with potential damage to the ocular surface and is due to increased osmolarity of tear film and inflammation of ocular surface according to International Dry Eye Workshop (2007). Medical students are often affected with dry eyes due to use of projectors, computers for study and also due to use of mobiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Visual analysis is a new analysis method; it is used in the field of mental health; under the influence of visual analysis, many characteristics of mental health are beginning to show up, but research on this aspect is still in its infancy. Simultaneously showing the mental state and personality characteristics through visual analysis, there are relatively few research studies on mining potential information; visualization converts data into visual elements such as graphics, symbols, colors, and textures that are easily perceivable by the human eye, and it can effectively enhance the efficiency of feature recognition and efficiently transmit valuable information [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Visual analysis is a new analysis method; it is used in the field of mental health; under the influence of visual analysis, many characteristics of mental health are beginning to show up, but research on this aspect is still in its infancy. Simultaneously showing the mental state and personality characteristics through visual analysis, there are relatively few research studies on mining potential information; visualization converts data into visual elements such as graphics, symbols, colors, and textures that are easily perceivable by the human eye, and it can effectively enhance the efficiency of feature recognition and efficiently transmit valuable information [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…16 The association between mental health and its negative effect on dry eye symptoms and pain has been demonstrated in literature. [17][18][19][20][21][22][23] Individuals with underlying mental illness such as anxiety, depression, or post-traumatic stress disorder (PTSD) have been shown to have increased dry eye symptoms. 21 Siedlecki et al showed patients with greater ocular pain intensity had a higher likelihood of reporting a history of fibromyalgia, depression, anxiety, and migraines.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students are affected by dry eyes because of their use of projectors and computers for academic purposes, and long periods of reading and exposure to screens. Several studies have been conducted to evaluate the prevalence of dry eye disease among medical students, and the results showed that the prevalence rates were ranging from 27.1% to 58% (Hyon et al, 2019;Laad et al, 2019).…”
mentioning
confidence: 99%
“…Despite the fact that DED and depression are prevalent among medical students (Hyon et al, 2019;Laad et al, 2019;Siddiqui et al, 2020), the characteristics of DED and their relationship to depression have not been studied adequately. Thus, this study aims to explore the association between DED and depression among medical students of Umm Al-Qura University, Saudi Arabia.…”
mentioning
confidence: 99%